2003
DOI: 10.1034/j.1600-0854.2003.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule‐Dependent Transport of Secretory Vesicles in RBL‐2H3 Cells

Abstract: Antigen-mediated activation of mast cells results in Ca 2+ -dependent exocytosis of preformed mediators of the inflammatory response. To investigate the role of secretory vesicle motility in this response, we have performed time-lapse confocal microscopy on RBL-2H3 cells transfected with a green fluorescent protein-Fas ligand fusion protein (GFP-FasL). Green fluorescent protein-labeled vesicles exhibit rapid, bidirectional movement in both resting and activated cells and can be localized adjacent to microtubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
86
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 30 publications
(32 reference statements)
20
86
1
1
Order By: Relevance
“…Microtubules are involved in mast cell degranulation, because the movement of secretory granules depends on intact microtubules (16,17). This finding is supported by demonstrations that agents inhibiting tubulin polymerization also suppress degranulation (18)(19)(20).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Microtubules are involved in mast cell degranulation, because the movement of secretory granules depends on intact microtubules (16,17). This finding is supported by demonstrations that agents inhibiting tubulin polymerization also suppress degranulation (18)(19)(20).…”
supporting
confidence: 70%
“…Accumulating recent data point to an important role of microtubules in these processes (38). Previous studies focused primarily on the role of microtubules in granular transport (13,16,17,20) or on the initial stages of SOCE signaling pathway (13,15,39). In this study, we show that microtubule network rearrangement in activated BMMCs and formation of microtubule protrusions is dependent on the activity of Ca 2+ sensor STIM1.…”
Section: Discussionmentioning
confidence: 53%
“…Microtubules, built up from ab-tubulin heterodimers, are important for mast cell degranulation, because the movement of secretory granules depends on intact microtubules (2,3), and compounds inhibiting tubulin polymerization suppress degranulation (4). It was reported that FcεRI aggregation leads to reorganization of microtubules (3,5) and that the influx of Ca 2+ plays a decisive role in microtubule remodeling (6,7).…”
mentioning
confidence: 99%
“…Following antigen stimulation and receptor crosslinking the intracellular signaling cascade is initiated. This cascade results in secretory vesicles fuse to the cell membrane and release their contents into the extracellular space [2]. While the identity of these and other molecular players are known, as well as their relative roles in immune response signaling cascades, relatively little work has been done in studying immune response in the stochastic regime.…”
mentioning
confidence: 99%
“…Vital to a comprehensive understanding of immune responses is the early spatial-temporal behavior of proteins at the membrane. We chose to study the dynamics of the high-affinity IgE receptor (FcεRI) in mast cells [1,2] following addition of its stimulatory ligand dinitrophenol (DNP). This system represents a well-studied, yet not fully understood molecular mediator of acquired immune system stimulation.…”
mentioning
confidence: 99%